Bifunctional aluminum porphyrin complex: Soil tolerant catalyst for copolymerization of 2 and propylene oxide. Issue 16 (12th June 2014) - Wu, Wei; Sheng, Xingfeng; Qin, Yusheng; Qiao, Lijun; Miao, Yuyang; Wang, Xianhong; Wang, Fosong
ABSTRACT Due to the concern on residue toxic metal in biodegradable poly(propylene carbonate) (PPC), soil tolerant and heavy metal free aluminum complexes, that is, bifunctional aluminum porphyrin catalysts bearing quaternary ammonium salts on the ligand framework were prepared. Variation of the quaternary ammonium anion and the axial ligand had dramatic effects on the catalytic activity of resultant complex, among which complex 3b yielded perfectly alternative PPC with high molecular weight and relatively narrow polydispersity, and its TOF reached 3, 407 h−1 at [PO]/[cat.] ratio of 20, 000 at 110 °C, although the PPC selectivity was 71%. By introducing specific substituent on the ligand framework, the electronic environment at the active center can be changed, among which complex 5b bearing tertiary butyl‐functionalized aryl substituents exhibited a TOF of 449 h−1 at [PO]/[cat.] ratio of 5, 000 at 70 °C, with PPC selectivity of 92% and number average molecular weight of 36 kg mol−1. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 2346–2355